Primary Education Teacher's Problem: Mobbing (Kastamonu Province Sample) - Ahi̇, Berat; Tabak, Hasan; Kaya, Gokhan (Elsevier BV, 2012)
AbstractIn this study, the professional terrorization imposed upon the teachers working at primary schools by the school managers has been studied in terms of the variables of gender and seniority. The research is a descriptive survey model study. The sampling of study is constituted by 268 primary school teachers working in the Central District of Kastamonu. As the data collection tool, the Negative Acts Questionnaire has been used in the study, which was developed by Einarsen and Raknes (1997) and translated into Turkish by Cemaloğlu (2007) and tested for validity and reliability. Among the findings of the study, it has been seen that the primary school teachers, in general, are not exposed to terrorization behaviors. It has been found that there is not any significant relationship between the studied variables of gender and seniority and the exposure to terrorization.
Keywords: teachers; Mobbing; primary schools; 4. Education; 16. Peace & justice